Recent advancement of sustainable and renewable energy in osmotic power generation - Yew, G.-Y. (Chulalongkorn University, Faculty of Fine and Applied Arts, 2021)
Investment in clean energy is demand in this century due to abundance of CO2 accumulation in the world to cause several environmental issues. Therefore, harvesting clean energy may assist in reducing carbon footprint in the world to create a green environment for sustainable living. The salinity gradient energy is one of the clean energies with the concept of mixing both salt concentration water from the ocean and fresh water from the river to create an osmotic pressure to power-up the generator for the production of electrical energy. Salinity different between the oceanic salt water and fresh water could produce an equilibrium osmotic pressure that achieve up to 27 bars equivalent from resulting pressure under the water for 200 to 300 meters. The potential of the power production through osmosis power generator is capture at the value of 2000 TWh per year, where in 2018 the world energy consumption was growing 2.3, in which twice the number compare to the average rate of the growth. The major energy consumption is contributed from fossil fuel and consequently resulted from emissions of CO2 increased to 33.1 Gt to the atmosphere. This work explained the advantage of using salinity gradient energy and the fundamental principle of blue energy from pressure-retarded osmosis (PRO). Thus, the osmotic power by using different salinity gradient to create energy is widely known as blue energy, in which it is green and sustainable to produce electricity to the local communities. Â© 2021, Chulalongkorn University, Faculty of Fine and Applied Arts. All rights reserved.